Smart Stock Verification System Using Android Application - S. M., Prathikksha; V., Juhishree; S., H. Prasanth; B., H. Krithik; P., N. Manivel; C., A. Devi (Indian Journal of Computer Science, 2021)
In recent years, the Android platform has gained popularity for its usability, availability, and low-cost handsets. Mobile technology is used to solve various problems in different fields. On an average any library of an institution will have at least a few thousand books. The books need to be brought to a scanner for verification which requires a lot of technical assistance. Stock verification is one such problem in a library. This process is tedious, time consuming and requires lot of manpower. There is hardly any problem in carrying a few books to the scanner, but this process becomes more difficult when a few thousand books need to be verified. Stock verification of books is a regular activity, which needs to be done every year. It is both cumbersome and error prone. Therefore, we propose an Android application. Barcodes can be scanned using the application and the corresponding status like available, mismatched, and traced will be tagged against the scanned book. This system will make the process of stock verification handy, unambiguous, and smooth.